Henry Clay the lawyer - Baxter, Maurice G. (Maurice Glen), 1920- (The University Press of Kentucky, 2015)
Though he was best known as a politician, Henry Clay (1777-1852) maintained an active legal practice for more than fifty years. He was a leading contributor both to the early development of the U.S. legal system and to the interaction between law and politics in pre-Civil War America. During the years of Clay's practice, modern American law was taking shape, building on the English experience but working out the new rules and precedents that a changing and growing society required. Clay specialized in property law, a natural choice at a time of entangled land claims, ill-defined boundaries, and.